Study of the Use of Antinematode Drugs, Mebendazole and Pyrantel, in Galicia (Spain) from 2016 to 2020 - S. Vázquez- Prieto; A. Vaamonde; E. Paniagua (Journal of Parasitology Research)
To the best of our knowledge, there is no study on the use of drugs focused on the consumption of antinematode drugs in any region of the world. In the present study, we analyzed and evaluated the use of mebendazole and pyrantel in the provinces of Galicia (Spain), as well as described the variability of the consumption of both drugs between these provinces from 2016 to 2020. A descriptive, cross-sectional, and retrospective study of the consumption of these drugs, expressed in defined daily dose per 1000 inhabitants per day (DHD), was carried out. The DHD values for both drugs were small, although clearly higher, both on average and in variability, in the case of mebendazole. The difference in the mean DHD between both drugs and the geographical differences observed was statistically significant. The seasonal differences were statistically significant for both active principles, with lower values in summer. The active principle most consumed in all the provinces and years was mebendazole. The main consequence of the excessive use of this drug compared to pyrantel may be the increased risk of the development of resistance and of therapeutic failure, as well as the consequent limitation of pharmacological options in the future.